Delayed Puberty, Eroticism, and Sense of Smell, a Psychological Study of Economic and Social Consequences (Kallmann's Syndrome): A Rare Case Report - Azlansyah Azlansyah; Cennikon Pakpahan; Hermansyah Hermansyah; Faisal Yusuf Ashari; Gustavo Santos Rainato; Kenley Nathanael; Maxwell Salvador Surya Atmaja (Wolters Kluwer - Medknow Publications, 2024)
Kallmann syndrome is defined as the association of hypogonadotropic hypogonadism and anosmia or hyposmia caused by abnormal migration of olfactory axons and neurons producing gonadotropin-releasing hormone. It is a nonlife-threatening disease with relatively good treatment. However, the effects of the condition persist throughout the affected individuals' lifetimes, leading to significant economic and social consequences. A man presented with eunuchoid body proportions complains about the size of his penis, absence of hair throughout the body, micropenis, and small testicles. Associated findings included hyposmia and a high-pitched voice. The patient experiences psychosexual impacts as a result of this illness. The patient could not undergo treatment to alleviate his genital size concern due to financial constraints as the treatment was not covered by government insurance.